2007
DOI: 10.2340/16501977-0111
|View full text |Cite
|
Sign up to set email alerts
|

Hand impairments and their relationship with manual ability in children with cerebral palsy

Abstract: Objective: To study hand impairments and their relationship with manual ability in children with cerebral palsy. Design: Cross-sectional survey. Patients: A total of 101 children with cerebral palsy (mean age 10 years, age range 6-15 years) were assessed. Methods: Three motor and 3 sensory impairments were measured on both hands. Motor impairments included grip strength (Jamar dynamometer), gross manual dexterity (Box and Block Test) and fine finger dexterity (Purdue Pegboard Test). Sensory impairments include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 8 publications
4
91
0
2
Order By: Relevance
“…Slower speed of movements 15 has been shown with both hands during keyboarding that requires finger aiming and repetition. 13 When the hemiplegic hand is being challenged, mirror movements can occur at the same time in the dominant hand. 14 Subtle deficits in fingertip forces have been observed in the sequencing of the grip-lift movement 5 and fine-finger dexterity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Slower speed of movements 15 has been shown with both hands during keyboarding that requires finger aiming and repetition. 13 When the hemiplegic hand is being challenged, mirror movements can occur at the same time in the dominant hand. 14 Subtle deficits in fingertip forces have been observed in the sequencing of the grip-lift movement 5 and fine-finger dexterity.…”
Section: Discussionmentioning
confidence: 99%
“…Is the contralateral hand a "good," 9 "unimpaired" 2,4 hand" or does it have "subtle deficits" 3e6, 9,10 ? Some authors have reported delays in the development of anticipatory control of grasp formation, 11 speed in movements, 12 fine finger dexterity, 13 and mild sensory impairments in the contralateral hand. 2,8 Children with hemiplegic cerebral palsy may present with substantial deficits in hand function, because bimanual activities involve the ability to use the affected and contralateral hands together for grasp and stabilization.…”
mentioning
confidence: 99%
“…To assess the subjective outcome, patient satisfaction regarding wrist function, cosmetic appearance and pain was documented using Visual Analogue Scales (VAS). The ABILHANDS-kids questionnaire was used to assess hand function in daily activities [26,27]. Overall outcome was graded according to the criteria of Price et al [8,28].…”
Section: Methodsmentioning
confidence: 99%
“…Cerebral palsy (CP) is the most prevalent form of physical disability in children (1), occurring in 1 out of 303 live births (). Almost 50% of children with CP present an arm–hand dysfunction (2, 3). Children with unilateral spastic CP seldom use their paretic hand spontaneously in daily activities (2, 4).…”
Section: Introductionmentioning
confidence: 99%